SMOKING'S ROLE IN THE PATHOGENESIS OF BRONCHIAL AND SYSTEMIC INFLAMMATION AT THE INITIAL STAGE COPD - A. E. Shuganov; N. A. Raspopina; J. M. Salmas; F. N. Paleev; E. G. Shuganov (SINAPS LLC, 2017)
COPD is characterized by a pathological inflammatory response in the lungs. Inflammation is qualitatively and quantitatively different from that  of smokers and persons without nicotine addiction. There is evidence for the presence of systemic inflammation in COPD, which probably originates in the lungs. Immune system was investigated on the basis of blood cytotoxic lymphocytes such as cytotoxic T - lymphocytes and NK - cells in patients with COPD 2 tbsp. The study included 42 patients with COPD severity according to 2 g (22) GOLD 2014 criteria. 22 patients with COPD 2 tbsp had smoking index of at least 20 pack \ years and 20 patients who had never smoked. In all patients, there were no data on atopy and asthma history. All surveyed patients received inhaled M-holinolitik - tiotropium bromide monohydrate 18 micrograms, and on-demand short-acting bronchodilators for 2 breaths. Age of patients was 1 group (smokers) from 50 to 62 years (mean age 54,1±1,3 years) .2 The second group - 58-75 years (58,21±0,7 years). By indirect immunofluorescence  were determined  relative and absolute  content  in peripheral blood lymphocytes, ekspresiruyuschie antigens CD3, CD4, CD16, CD20, CD23, CD25, CD54, CD71, CD72, HLA-DR, CD95, membrane  immunoglobulin mIgM and mIgG. As a result of the study it was found that  patients  in the early stages of COPD 2 tbsp. there was a significant change in blood levels of cytotoxic lymphocytes,  regardless of the addiction to smoking. But when smoking signs "oxidative stress" are more pronounced,  resulting in a more rapid and possibly further more severe course of the disease. Thus, COPD is characterized by the development  of systemic inflammation, however, the underlying mechanisms, as well as the desirability and feasibility of the suppression of inflammatory processes require further study.